The Carbon of Swietenia Machrophylla Fruit Peel and Coal Fly Ash as Bio-Composite Brake Ingredients (Jurnal Bahan Alam Terbarukan, 2022)
The eco-friendly brake composite has been still an interesting issue in the development of brake friction materials. Wastes of S. Macrophylla (mahogany) fruit skin and coal fly ash are available as organic ingredients of bio-composite brakes. In this research, we investigated the effects of both ingredients on the brake composite properties which were fabricated using hot isostatic pressing at temperature 200 °C and pressure 5 kN for 3 h. The specimens were prepared in some volume fractions of carbon (2 vol% - 12 vol%). As a result, several tested specimens containing mahogany fruit skin carbon revealed maximum Rockwell hardness 69 HRB, wear 2.49x10-4mm2/kg, and water absorption 2.72 %, while specimens containing coal fly ash showed 78 HRB, 1.1x10-3mm2/kg, and 3.5 %, respectively. The brake composites containing coal fly ash performed better than ones containing mahogany fruit skin carbon. The hardness and wear of these two types of brake composite friction materials meet the minimum criteria required by SAE, JA661, and are close to the quality of the brake pads of two commercial brake composite materials. Water absorption in the brake lining specimens with mahogany leather carbon showed that the addition of the volume fraction caused an increase in water absorption, while the specimen containing coal fly ash showed that the increase in the carbon volume fraction caused a decrease in water absorption.